POLA PENANGANAN KONFLIK AKIBAT KONVERSI AGAMA DI KALANGAN KELUARGA CINA MUSLIM - Elizabeth, Misbah Zulfa (WALISONGO, 2013)
AbstractThis research has the purposes to reveal the patterns of conflict caused by religiousconversion among Chinese Muslim in Semarang, the patterns of conflict resolutionapplied among them, and their view on the conflict resolutions applied. Applying themethods of interviewing using structured interview guidance, participationobservation, and deep interview, it was revealed that there are five kinds of conflictcome out of conversion: indifference, teasing allusion, rude speaking, rejection, andhostile. Meanwhile there are three ways found in resolving conflict caused byreligious conversion: to let the conflict goes on and resolved by time, to explain theproblem related to Islam, and to go out from family circle. Based on the varieties inresolving the conflict, it is revealed that the community tends to approve the peaceway in solving any problem, otherwise it will break the value the community hold,harmony.***Penelitian ini bertujuan untuk mengungkap pola konflik yang disebabkan olehkonversi agama di kalangan Cina Muslim di Semarang, pola resolusi konflik yangditerapkan di kalangan mereka, serta pandangan mereka mengenai penyelesaianyang mereka lakukan, Dengan menggunakan metode wawancara denganpedoman wawancara terstruktur, observasi partisipasi, observasi, dan wawancaramendalam ditemukan bahwa ada lima bentuk konflik akibat konversi: tidakdipedulikan, digoda, bicara kasar, penolakan, dan permusuhan. Sementara ituditemukan tiga cara penyelesaian konflik, yaitu membiarkan masalah sehinggahilang bersama waktu, menjelaskan tentang Islam, dan keluar dari lingkupkeluarga. Berdasarkan keragaman cara penyelesaian masalah tampak bahwakomunitas Cina cenderung menggunakan cara damai dalam menyelesaikanmasalah.Keywords: konflik, resolusi konflik, konversi agama, Cina Muslim, harmoni